(untitled) (Praxis Educativa, 2012)
Both in the academy and in the Superior Institutes for Training Teachers (ISDF, according to its Spanish acronym) it is often insisted today on the political dimension of reading and writing as devices of social inclusion, by thinking not only about the individuals undergoing a pedagogic experience and of the processes of acquisition and transmission of knowledge, but also by taking into account the social actors in general in their daily situations. For that reason, according to my role as teacher of teachers in the U.N.C. (National University of Córdoba) and taking the fieldwork of two researach projects –one carried out by the Foundation Lúminis and the UDESA and the other one inscribed in Secyt, U.N.C.-, I set out to reconsider how would-be teachers read and write, what representations these agents have of these language practices, and what initiatives are put forward in the institutions when it comes to thinking of language as a resource to teach and learn.